A rare case of Bochdalek diaphragmatic hernia with concomitant partial situs inversus - Jain, Rishabh; Gujar, Ajay; Khan, Naseem; Sreedharan, Lokesh; Shaikh, Tanveer Parvez; Palresha, Roshan; Burra, Chaitanya (International Journal of Research in Medical Sciences, 2017)
Congenital diaphragmatic hernias clinically presenting in adulthood are exceedingly rare lesions, mainly left-sided defect (Bochdalek). Bochdalek hernias most commonly manifest during the patient’s first few weeks of life. Diagnosis beyond the first 8 weeks of life is estimated to represent 5-25% of all Bochdalek hernias. Here we have a 32 year old female patient who presented with 10x10 cm diaphragmatic hernia with dextrocardia who was asymptomatic for years.